Navigation in Oral and Maxillofacial Surgery Applications, Advances, and Limitations - Parhiz, Seyed Alireza; James, Jeffrey N.; Ghasemi, Shohreh; Amirzade-Iranaq, Mohammad Hosein; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers a comprehensive overview of the fundamentals of navigation surgery in the head and neck region. Navigation is particularly important in difficult and limited exposure areas, such as the orbit and deep spaces of the head and neck. With the aid of navigation systems, an expert can palpably and accurately measure the amount of bone removed during fracture reductions or resections of bony masses procedures. In addition to reducing surgery time for soft tissue lesions, navigation technique also allows for minimally invasive access to lesions without extensive dissection that is often required for traditional open approaches. Navigation can also be extremely helpful in locating and retrieving foreign bodies. Chapters cover navigation in a variety of different surgical specialties including, but not limited to, trauma surgery, implant surgery, and orthogenetic surgery. Chapters also discuss surgical pathology as well as guided surgeries. The book features detailed case presentations for each surgery sub-topic and discusses future advances in the field that are currently in development. Navigation in Oral & Maxillofacial Surgery is a must-have resource for clinicians, professionals, and practitioners in the fields of oral & maxillofacial surgery, otorhinolaryngology-head & neck surgery, trauma surgery, and plastic surgery, as well as researchers and postgraduate students in related fields.
Fundamentals of Navigation surgery -- Navigation in Orthgnatic surgery -- Navigation in Trauma surgery -- Navigation in surgical pathology -- Navigation in Implant surgery -- Navigation & guided surgery.
Keywords: Mouth$1 (BSurgery.s; Oral and Maxillofacial Surgery; Oral Surgical Procedures; Surgical Navigation Systems; Surgery, Computer-Assisted; Mouth -- surgery